Pengaruh Fluktuasi Harga Emas, Literasi Keuangan dan Pendapatan terhadap Keputusan Investasi Emas : Pada Member Agen Mini Gold di Kota Demak - Wahyuningsih ED; Aniqotunnafiah Aniqotunnafiah; Khoiriyah SN (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to determine and test the effect of gold price fluctuations, financial literacy and income on gold investment decisions, on research subjects (respondents), namely members who are members of the minigold distributor agent in Demak City. This type of research is quantitative research, using primary data. The primary data collection instrument used a questionnaire (Google form) in an online survey aimed at respondents, via a smartphone. (respondents fill in/check one of the answers that are considered the most appropriate. The scale used in the questionnaire is the Likert scale, to measure the opinions/perceptions of respondents. The population in this study were all members of the minigold distributor agent in Demak City. The sampling technique was saturated sampling or census, namely the entire population was part of the sample. The dependent variable of this study was Gold Investment Decisions, while the independent variables were Gold Price Fluctuations, Financial Literacy and Income (respondents). The analysis method used was Multiple Linear Regression. The results of the study are as follows: 1) Gold price fluctuations do not affect gold investment decisions, 2) Financial literacy has a positive and significant effect on gold investment decisions, and 3) Income has a positive and significant effect on gold investment decisions